Poly-β-D-(1,6)-N-acetyl-glucosamine (PNAG) glycan vaccines with broad spectrum neutralizing activities - Kuo-Shiang Liao; Mu-Rong Kao; Tzu-Hsuan Ma; Mei-Hua Hsu; Tzu-Yin Chen; Balázs Imre; Philip J. Harris; Jiun-Jie Shie; Cheng-Hsun Chiu; Chung-Yi Wu; Yves S. Y. Hsieh (Nature Communications)
Abstract The development of bacterial vaccines is a complex challenge due to the substantial serological diversity of protective antigens. One promising antigenic target is the conserved surface polysaccharide poly-β-(1,6)-N-acetyl-D-glucosamine (PNAG). Despite its widespread distribution, antibodies raised against PNAG have shown restricted efficacy in promoting microbial elimination in vitro and safeguarding against infections in vivo. Systematic studies and vaccine development have been hindered by limited knowledge of optimal antigenic features, such as chain length and degree of N-acetylation. Here, we describe an effective n + 2 glycosylation strategy enabling controlled synthesis of partially (dPNAG) and fully deacetylated PNAG glycans. Glycan microarray analysis shows that dPNAG glycans with DP8 and DP12 are optimal, with corresponding protein conjugates eliciting the highest IgG titers. Sera containing antibodies against the dPNAG DP8 conjugate with 40% acetylation exhibit the best opsonic activity against three prevalent nosocomial pathogens and confer the highest protection in female BALB/c mice against Staphylococcus aureus, supporting its potential as a vaccine candidate.